EFEKTIVITAS DAN BIAYA SEFALOSPORIN PADA PASIEN SIROSIS HEPATIS DENGAN RISIKO SPONTANEOUS BACTERIAL PERITONITIS DI RUMAH SAKIT ROYAL PRIMA PADA TAHUN 2022-2025 - Grace Kristin Sonayania Dakhi; Daimah Wirdatus Sanaun Harahap; Astriani Natalia Br Ginting (Jurnal Buana Farma, 2026)
Hepatic cirrhosis is a chronic liver disease often accompanied by serious complications, one of which is spontaneous bacterial peritonitis (SBP), which plays a significant role in increasing morbidity and mortality. Third-generation cephalosporin antibiotics, such as cefotaxime and ceftriaxone, are widely used as first-line therapy in patients with hepatic cirrhosis at risk of SBP. However, the increasing incidence of bacterial resistance and the high cost of treatment require an evaluation of the clinical effectiveness and cost-efficiency of the therapy provided. This study aims to assess the effectiveness and cost of using cephalosporin antibiotics in patients with hepatic cirrhosis at risk of SBP at Royal Prima Hospital Medan during the period 2022–2025. This study uses a pharmacoeconomic approach in the form of Cost-Effectiveness Analysis (CEA) to assess the cost-effectiveness of cephalosporins based on the relationship between treatment costs and patient clinical outcomes. Cost-effectiveness is assessed through the calculation of the Cost-Effectiveness Ratio (CER). The results show that the characteristics of patients are predominantly male and in the adult to elderly age group. This finding is in line with the epidemiological characteristics of liver cirrhosis which is more common in men, especially due to long-term risk factors such as chronic liver disease and alcohol consumption. The study shows that the analysis of the Cost-Effectiveness Ratio (CER) and Cost-Effectiveness Analysis (CEA) values has a positive and significant effect on total medical costs, which indicates that increasing costs per unit of clinical outcomes will have a direct impact on increasing total treatment costs.